SEAFARING WOMEN : An Investigation of Material Culture for Potential Archaeological Diagnostics of Women on Nineteenth-Century Sailing Ships - Seaborn, R. Laurel (East Carolina University, 2014)
During the 19th century, women went to sea on sailing ships. Wives and family accompanied captains on their voyages from New England. They wrote journals and letters that detailed their life on board, adventures in foreign ports, and feelings of separation from family left behind. Although the women kept separate from the sailors as class and social status dictated, they contributed as nannies, nurses and navigators when required. Examination of the historical documents, ship cabin plans, and photos of those interiors, as well as looking at surviving ships, such as the whaleship Charles W. Morgan, provided evidence of the objects women brought and used on board. The investigation from a gendered perspective of the extant material culture, and shipwreck site reports laid the groundwork for finding potential archaeological diagnostics of women living on board.
Keywords: Archaeology; American history; Women's studies; Gender analysis; Maritime; Material culture; New England; Nineteenth century; Shipwrecks; Women--Social conditions--19th century; Sailing ships--19th century; Charles W. Morgan (Bark)